Effects of a 10-week athletic performance program on match performance variables in male professional football players - Jiménez Rubio, S.; Estévez Rodríguez, J. L.; Escamilla Galindo, V.; Jiménez-Sáiz, S. L.; Del Coso, J. (Frontiers in Sports and Active Living, 2025)
Introduction: The aim of this study was to evaluate the effect of an Athletic Performance Program (APP), implemented as a complement to the usual training routines of a professional football team, on match performance variables in professional football players. The APP was designed to target mobility, stability, strength, multidirectional and sprint skills, which are critical for performance during competitive matches.